2005
DOI: 10.1111/j.1398-9995.2005.00725.x
|View full text |Cite
|
Sign up to set email alerts
|

Nasal polyposis and its impact on quality of life: comparison between the effects of medical and surgical treatments

Abstract: These results suggest that NP has considerable impact on a patient's QoL and that both medical and surgical treatment led to similar effects in improving QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
148
3
8

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(162 citation statements)
references
References 36 publications
3
148
3
8
Order By: Relevance
“…In fact, the MCS scores were slightly higher in MCS (50.6 versus 47.69), although they were lower than the values found in the Spanish general population (MCS ϭ 79.7; PCS ϭ 78.8). 12 It has been shown that patients with NP have lower scores in SF-36 than patients with coronary artery disease, asthma, and chronic obstructive pulmonary disease. 30,31 Hissaria et al 32 published the only study focusing specifically on NP using a modified RSOM-31 questionnaire.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the MCS scores were slightly higher in MCS (50.6 versus 47.69), although they were lower than the values found in the Spanish general population (MCS ϭ 79.7; PCS ϭ 78.8). 12 It has been shown that patients with NP have lower scores in SF-36 than patients with coronary artery disease, asthma, and chronic obstructive pulmonary disease. 30,31 Hissaria et al 32 published the only study focusing specifically on NP using a modified RSOM-31 questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…We used a generic questionnaire, the SF-12, and a specific questionnaire, the RSOM-31. Radenne et al 11 and Alobid et al 12 measured the QoL in patients with NP using the SF-36 questionnaire. Both studies showed significant differences between healthy subjects and patients with NP in all the SF-36 domains, except for physical functioning in Alobid et al 12 Moreover, they also found that patients with NP had lower scores in the MCS than in the PSC, which suggests that NP has a greater impact on mental health than on physical health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same group (Alobid et al, 2005) compared, in a randomized trial, medical treatment (53 patients, oral prednisone for two weeks) and surgical treatment (56 patients undergoing ESS) of CRS with nasal polyps. Both groups received intranasal budesonide for 12 months after intervention.…”
Section: Effect Of Rhinosinusitis Treatment On Quality Of Lifementioning
confidence: 99%
“…A large number of studies have demonstrated poor health-related QoL in NP as well as in asthma with respect to both generic and specific aspects of QoL [7]. NP and asthma symptomology is likely to contribute to poor psychological well-being, of which important aspects include anxiety, mild depression and low vitality, making these patients particularly prone to improvement in psychological aspects of QoL [8]. Support for this has recently been reported from patients with NP and asthma, by assessment with the Short Form 36 (SF-36) [9].…”
Section: Introductionmentioning
confidence: 99%